Fractionated Mapping-Guided Ablation Strategy in Patients with Long-Standing Persistent Atrial Fibrillation: a Case Series - Aksu, Tolga; Guler, Tumer Erdem; Bozyel, Serdar; Yalin, Kivanc (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Although pulmonary vein isolation (PVI) remains the cornerstone of ablation for paroxysmal atrial fibrillation (AF), optimal ablation strategy for long-standing persistent AF (LSPAF) remains unclear. This article presents two patients with LSPAF in whom acute AF termination was achieved during ablation by using fractionated-guided extended PVI, posterior wall isolation, and mitral isthmus.